"Postcolonializing" Deleuze: Transnationalism and horizontal thought in the British South Asian diaspora - Pervez, Summer (University of Ottawa (Canada), 2007)
This dissertation is about the need to re-examine South Asian British literature and film from the perspective of "horizontal" thought. Writers and filmmakers of the British Asian diaspora offer a new model of thinking about identity, one that is "Deleuzean" in nature. Artists such as Salman Rushdie, Hanif Kureishi, Meera Syal, Monica Ali, Suniti Namjoshi, and Gurinder Chadha reveal a concern with showing both celebrations of and resistance to pluralism and possibility in a transnational world. Furthermore, their work also illustrates the need and desire to create a new cultural poetics in Britain, one that is more inclusive of diaspora literature and film. When applied to Asian British texts, Deleuzean philosophy reveals the complex intersections of migrancy, ethnicity, postcoloniality, and (homo)sexuality in the diasporic identities of contemporary South Asian writers, filmmakers, and their characters. In contrast to models of hybrid identity espoused by postcolonial theorists such as Homi Bhabha (vertical thinkers), Gilles Deleuze's model of horizontal thought escapes hierarchism, binarism, and idealism when analyzing transnational, liminal identities as represented in and by the creative work of British Asians. This shift in thought to horizontality is necessary because the literature and film themselves exemplify the following three concerns: (1) the need and quest for plural identities, (2) an examination of the pros and cons of being a migrant/transnational/diasporic figure in England, calling for a consideration of both transnationalism's advantages and its discontents, and (3) and the need to create a unique cultural poetics that operates as a "minor" literature that forms a significant part of the larger grouping of English literature and cinema.
Keywords: Literature, Asian.; Literature, English.